Röntgenographische und spektroskopische Untersuchung einiger Strontium- und Zink-substituierten Calcium-Fluorapatite - Apella, María Cristina (1989)
Simultaneous strontium and zinc substitution for calcium in the fluoroapatite lattice was investigated. Crystallographic data for different members of the series Ca10-x-ySrxZny(PO4)6F2 were obtained from X-ray powder diagrams. The effects of the substitutional process on the strength of the phosphate P-O-bonds were checked by Raman spectroscopy. For comparative purposes, the first members of the series Sr10-xZnx(PO4)6F2 were also investigated in a similar way.